Empire of Lahburn / Nur Fahira Abdul Halim ... [et al.] - Abdul Halim, Nur Fahira; Suduki@Yahaya, Nor Fatin Nabilah; Abdul Razak, Nur Liyana Syamimi; Ramli, Nurulhuda Ainaa; Kamarudin, Nurhafizah (2021)
Entrepreneurship is a study of the concept and process of an entrepreneur in needing a business or someone who risks their finances in order to expect a profit. In the study involves the field of the Faculty of Film, Theater and Animation, which expresses knowledge of the process of how to become a successful entrepreneur. In this study we were given an explanation of Go-Ecommerce where the platform teaches how the process of becoming a thriving and successful entrepreneur. In Go- Ecommerce also teaches how to use platforms such as Facebook, Instagram and others to improve product quality as well as get customer response. In addition, through entrepreneurship can also create confidence in a person to change the world through ideas and innovation. An individual’s confidence and courage towards the risks faced in developing ideas and innovations through an established organization can thrive. Therefore, for this group assignment, we have chosen the “Empire of LahBurn” as a study on entrepreneurship of the company. For this case study the group was assigned to interview one of the managers from the company. ENT530 is a Principle of Entrepreneuship subject which is a compulsory subject to be studied in the FF237 Film Production program.